The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/s0100-204x2016000600010
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento compensatório e privação alimentar no desempenho produtivo do robalo-flecha

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da privação alimentar e a ocorrência de crescimento compensatório sobre o desempenho produtivo de formas jovens do robalo-flecha (Centropomus undecimalis). O experimento teve duração de 60 dias, em que os peixes -35 indivíduos por tanque -foram divididos nos três seguintes grupos de tratamentos: com alimentação todos os dias (controle); com alimentação cinco dias por semana, seguidos de dois dias de jejum; e com alimentação quatro dias por semana, seguidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies on CG are more common in fish (El Ghazali et al, 2009; Herrera et al, 2016; Oliveira et al, 2020) and prawns (Marques & Lombardi, 2011; Wei et al, 2008; Wu et al, 2001). In molluscs, Fermin (2002) described the occurrence of full CG in abalones ( Haliotis asinina ) after periods of feed restriction, whereas Auster and Stewart (1984) found that Argopecten irradians scallops presented CG characterized by faster growth after spawning, than slow prespawning growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on CG are more common in fish (El Ghazali et al, 2009; Herrera et al, 2016; Oliveira et al, 2020) and prawns (Marques & Lombardi, 2011; Wei et al, 2008; Wu et al, 2001). In molluscs, Fermin (2002) described the occurrence of full CG in abalones ( Haliotis asinina ) after periods of feed restriction, whereas Auster and Stewart (1984) found that Argopecten irradians scallops presented CG characterized by faster growth after spawning, than slow prespawning growth.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms for compensatory growth are still poorly understood, but hyperphagia and feed efficiency are the physiological bases of compensatory responses, occurring simultaneously or not (Hayward, Noltie, & Wang, 1997; Sevgili, Hossu, Emre, & Kanyilmaqz, 2013; Urbinati et al, 2014). When feeding is restored, animals submitted to a food deficit become hyperphagic compared to fish maintained with a continuous ad libitum food supply, reflecting in daily feed consumption (Ali et al, 2003; Gonçalves et al, 2014; Gurney, Jones, Veitch, & Nisbet, 2003; Herrera, Silva, Santos, Sousa, & Sanches, 2016). In Perca flavescens , the end of hyperphagia occurred after 2 weeks of recovery and in Lates calcarifer juveniles, up to 21 recovery days.…”
Section: Discussionmentioning
confidence: 99%